Dogfight dari Sudut Pandang Teori Permainan - Rafi Prayoga Dhenanta; Aditya Purwa Santika (The Indonesian Journal of Computer Science, 2025)
Dogfight is one of many scenarios happening in a battle for air-superiority. This research delves deeper into dogfight, using the perspectives of game theory. The purpose of this research is to model a strategy that can be used in a dogfight. This research models dogfight into game theory’s extensive-form-games and then simulates the model ccompuationally. From the simulation, the model developed in this research increases the winning rate of a certain player significantly.